PENGALAMAN MAHASISWA PROGRAM STUDI PENDIDIKAN NERS DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Richel Febiola Nadya Gultom; Evelyn Hemme Tambunan (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Covid-19 pandemic has affected all aspects of human life globally, including aspects of education. The policy to minimize the spread of Covid-19 has an impact on the implementation of online learning policies to replace face-to-face learning in the classroom. The changes that occur produce distinguish experiences from previously. The purpose of this study was to explore the experiences of students in the academic stage of the Ners education study program while participating in online learning in the academic year of 2019/2020 and odd 2020/2021 at the Faculty of Nursing, Universitas Advent Indonesia.. This study utilized a qualitative research design with a descriptive phenomenology approach. Through in-depth interviews using semi-structured questions to 8 students from different education levels in collecting data. The data analyzed in an organized manner to obtain positive and negative experience categories. The positive experience category has 7 sub categories and negative experience has 8 sub categories. Online learning experiences provide an overview of increasing the effectiveness of online learning to produce professional nurses.